Tax Policy for Developing Countries - Tanzi, Vito.; Zee, Howell (Washington, D.C. : International Monetary Fund, 2001)
Discusses important tax policy issues facing developing countries today, provides a review of the role of tax incentives, and identifies some policy challenges posed by the globalization of the world economy. Draws on country cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet